An investigation into the style and asset class adjusted performance of South African multi-asset funds - Richardson, Luke A.C. (Department of Finance and Tax, 2020)
Purpose: This study examines 26 large and established South African multi-asset unit trusts in order to determine their style and asset class exposure over time. The objective is to ascertain whether South African multi-asset fund managers can realise outperformance, that exceeds what can be realised through exposure to representative, investable, style and asset class indices. Such an analysis assists in identifying unit trust manager skill, but a further consideration is how to combine unit trusts in a suitable manner, to this end portfolio construction tools are utilised to meet illustrative client objectives in a multi-asset context. Methodology: This study uses monthly total return time series for several investable style and asset class indices as well as South African multi-asset unit trust monthly total return time series. Where historical data permits, the period under investigation is from 1 January 2003 to 30 June 2018. Style and asset class exposure is determined using the Returns Based Style Analysis (RBSA) of Sharpe (1992) applying a 24-month rolling window approach. Findings: The equity style exposures estimated using RBSA provide evidence that on average the value style was dominant across the multi-asset high equity unit trusts examined. For the multi-asset low equity unit trusts examined the low volatility style was dominant. Moreover, a large proportion of the variability in returns of many multi asset unit trusts, can be explained by exposure to style and asset class indices. Consequently only 3 out of the 15 multi-asset high equity unit trusts analysed, could realise performance in excess of their custom style and asset class benchmark. As only a limited number of these unit trusts could demonstrate superior security selection ability the implication is that many asset managers stand to be disrupted by lower cost products that provide similar style and asset class index exposure. Originality/Value: Much research has been conducted into the style exposures of SA general equity funds. However, to the author’s own knowledge this is the first study to apply RBSA in a performance context to multi-asset unit trusts, under the new ASISA classification standards. The benefits of portfolio construction tools such as portfolio simulation and the ‘Risk Budgeting’ approach are also discussed and applied in a multi-asset context.